PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PERUSAHAAN DI INDONESIA - Umi Murtini; Rizal Mansyur (Jurnal Riset Akuntansi dan Keuangan, 2012)
This research aims to test the impact of corporate governance mechanism towards earnings management hold by Indonesian companies. The reseach explains the impact of manajerial,institusional ownership, independent commissioner, the size of commissioner council, and auditor quality (as corporate governance proxy) towards earnings management. The resultproves that manajerial ownership and independent commissioner give negative impact while commissioner council gives positive impact and institusional ownership and auditor qualitydo not affect the earnings management.Keywords: corporate governance, earnings management, auditor quality